Visual requirements and shooting performance of the elite biathlete - Wimshurst, Z. L.; Köykkä, M.; Ruotsalainen, K.; Linnamo, V. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Sports vision is a growing area of interest with increasing numbers of high performing teams dedicating time to test and train their visual system to improve competitive performance. However, the visual system consists of several components, or "visual skills," each of varying importance for sports and activities. Currently, there is no systematic way to determine which visual skills are most relevant for each sport. In a previous study, elite air rifle shooters demonstrated higher levels of accommodation than non-elite shooters, and all shooters had better visual acuity than non-athletes [1]. Yet, the study did not explain why the visual capabilities that they tested were considered crucial for shooting. This study aimed to design and use a questionnaire to identify which visual skills those involved in biathlon perceive to be important for sport`s shooting element and to test whether these identified visual skills correlate with key shooting technical components [2] and shooting performance in biathletes.